CONNECTICUT MFP PROGRAM PARTICIPANTS' EXPERIENCES: A QUALITATIVE STUDY. (11th November 2018) - Kellett, K; Ligus, K; Robison, J
Abstract: The Money Follows the Person Rebalancing Demonstration (MFP) is a federal initiative to help states transition people from institutional settings to the community to enhance individual preferences and rebalance Medicaid expenditures. Participants of this program provided qualitative feedback about perceived effectiveness of the program and identified barriers to successful program implementation. Data were collected from 1, 265 consumers who answered an open-ended question, "Is there anything else you would like to add, " in the Quality of Life Survey conducted from 2009–2016 at baseline, 6, 12 and 24 months after transition. ATLAS.ti software was used for data analysis, and Maslow's Hierarchy of Needs was employed as a thematic framework to categorize data. Outcomes show that while many respondents underscored the efficacy of the program and offered positive feedback, some also reported barriers and challenges. Of the 2, 274 comments, the most frequently reported theme was physiological needs, (e.g., personal assistance and assistive technology) (53%, n=1, 197). The second theme was safety-security needs(e.g., transportation and finances) (11%, n=252). Additional themes included social needs (e.g., support and social services) (23%, n=529), self-esteem needs (7%, n=16), and self-actualization needs (6%, n=128). While MFP consumers generally report high quality of life, both in the CT program and nationally, this study found that some participants could benefit from increased community services and supports to more fully meet their needs. Findings have the potential to deepen stakeholders' understanding of consumer needs and facilitate planning to improve services and supports for older adults and people with disabilities living in the community.